(untitled) (Latakia University Journal -Basic Sciences Series, 2018)
Flowers of Inula viscosa (L.) plant (Inula genus , Asteraceae family), locally known as Taion, was collected from two different regions of Lattakia: the Jubt Barghal region (a mountainous area), the Qaya region (a coastal area), and the essential oil was extracted by Hydrodistillation using the Cleveger apparatus , where the weight percentage of essential oil stood at 1.26%,1.1% for both mountainous and coastal region ,respectively. The Chemical composition of essential oil obtained from flowers of Inula viscosa (L.) was analyzed by GC/MS . The essential oil of the mountainous area contained 60 components, 58 components of which were identified, that accounting for (97.98%) of total essential oil. The main component controlling was: 7-methoxy-5-ethoxy-2,2-dimethyl-2H-chromene (43.43%) The essential oil of the coastal region contained 33 components, 32 components of which were identified, that accounting for (98.31%) of total essential oil. The main components were: Linalyl propionate (19.70%), Eugenol (15.11%), n-Eicosane (9.27%).